Modeling the Earth’s Crust Using Synthetic Receiver Function Data with Nearests Neighborhood Method - Wiwit, Suryanto (Physics Department Sebelas Maret University, 2011)
A study to model the Earth's crust from a receiver-function data have been carried out In this research we will dis cuss two methods which are member of a Monte Carlo family, i.e. Metropolis and Neighborhood search algorithm. Monte Carlo method was studied since the characteristics of receiver-function data that are usually mixed with coda waves that follow the P wave and S wave. Such a conventional methods (i.e. Marquadt-Lavenberg) was usually diffi cult to get the best model for a scatter data of this kind. The algoritm were tested using a synthetic data to see the per formance of this method. The results show that this method is good enough to get the desired velocity model. In the future this method will be used to process the real observation oata from MERAMEX project